Generating an African Palliative Care Evidence Base: The Context, Need, Challenges, and Strategies - Harding, Richard; Powell, Richard A.; Downing, Julia; Connor, Stephen R.; Mwangi-Powell, Faith; Defilippi, Kath; Cameron, Sue; Garanganga, Eunice; Kikule, Ekiria; Alexander, Carla (Journal of pain and symptom management, 2008)
The enormous burden of progressive, incurable disease in sub-Saharan Africa is reflected in the epidemiology of cancer and HIV. However, there has been little research activity and evidence generated to inform appropriate and effective responses. Acollaborative of clinicians, academics and advocates have been active in the design, delivery and reporting of research activites in African palliative care. Here, they report the methodological, ethical, logistic and capacity-based challenges of conducting research in the sub-Saharan context from their experience. A number of strategies and responses are presented.
Keywords: Africa; Research; Methodology; Review